Microstructure and Mechanical Properties of Aluminum Alloy/Stainless Steel Dissimilar Ring Joint Welded by Inertia Friction Welding - Qin, Feng; Zhang, Chunbo; Zhou, Jun; Xu, Kai; Wang, Qi; Li, Yunlei; Zhang, Wenhan (Frontiers in Materials, 2022)
In recent years, studying the weldability of a dissimilar metal hybrid structure, with the potential to make full use of their unique benefits, has been a research hotspot. In this article, inertia friction welding was utilized to join Φ130 forged ring of 2219 aluminum alloy with 304 stainless steel. Optical observation (OM), electron back scattering diffraction (EBSD), and scanning electron microscopy (SEM) were utilized to examine the joint microstructure in depth. Depending on the research, a significant thermal–mechanical coupling effect occurs during welding, resulting in inadequate recrystallization on aluminum-side thermo-mechanically affected zone (TMAZ) and forming zonal features. The crystal orientation and grain size of each TMAZ region reflect distinct differences. On the joint faying surface, the growth of intermetallic compounds (IMCs) is inhibited by a fast cooling rate and metallurgical bonding characteristics were found depending on the discontinuous distribution of IMCs. The average joint tensile strength can reach 161.3 MPa achieving 92.2% of 2219-O; fracture occurs on aluminum-side base metal presenting ductile fracture characteristics.